The Effectiveness of Grammarly Features in Building Arguments in Writing Essays - Muhammad, Garindra (Universitas Harapan Bangsa, 2024)
Technology has already taken over to affect the way languages are learned. Tools such as Grammarly have become trendy among students to improve their writing. One of the helpful things for a student to write an effective essay is to have assistance like proper tools and support for better writing, and one of them is using Grammarly. This study aimed to measure how Grammarly affected the ESL students’ writing provided in their essays, focusing on improvements in the build of the argument. This research also measured grammar, usage of tense, and overall structure. This research used mixed methods by collecting the data through essay assignment submission, taken both before and after using Grammarly. Each of the essays used as the assignment was a 5- paragraph essay consisting of an introductory paragraph, three body paragraphs, and a concluding paragraph. By comparing their essays from both stages, The results of this study show that Grammarly provided corrections not only for common mistakes such as grammar, misspellings, and inconsistent verb tense but also offered suggestions for improving sentence clarity. The analysis revealed an improvement of 60.24% in the clarity and structure of students’ arguments as Grammarly helped rewrite the sentences into more concise and well-structured complex and compound forms.